2003
DOI: 10.3989/gya.2003.v54.i4.219
|View full text |Cite
|
Sign up to set email alerts
|

Changes occurring in vegetable oils composition due to microwave heating

Abstract: Cambios producidos en la composición de aceites vegetales debido al calentamiento en microondas. Se estudia el efecto del calentamiento en horno de microondas sobre aceites de diferente composición en ácidos grasos. Aceites de girasol, soja, cacahuete y una mezcla de soja y cacahuete al 50%, se calentaron durante 2, 4, 6, 8 10, 12, 15 y 18 minutos. Los valores de índice de peróxidos, acidez libre y absorbancia a 420 nm fueron proporcionales al tiempo de calentamiento. Otras determinaciones incluyeron el conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
51
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 17 publications
9
51
1
2
Order By: Relevance
“…Low peroxide values and dienoic conjugation could explain the negligible changes of essential fatty acids observed during the microwave heating as reported in the literature (COSSIGNANI et al 1998;KIM & JOO 1995;HASSANEIN et al 2003), which is in agreement with the results of our preliminary experiments.…”
Section: Changes Of Conjugated Double Bond Systemssupporting
confidence: 93%
See 2 more Smart Citations
“…Low peroxide values and dienoic conjugation could explain the negligible changes of essential fatty acids observed during the microwave heating as reported in the literature (COSSIGNANI et al 1998;KIM & JOO 1995;HASSANEIN et al 2003), which is in agreement with the results of our preliminary experiments.…”
Section: Changes Of Conjugated Double Bond Systemssupporting
confidence: 93%
“…Free fatty acids present in oil enhance the oxidation ( YOSHIDA 1993), which may be important if cold-pressed unrefined oils are used in microwave treated systems. Similar results were obtained on comparison of sunflower, soybean, and peanut oils, and a mixture of soybean and peanut oils (HASSANEIN et al 2003). Five vegetable oils were treated in a microwave oven, and their stabilities were tested under Rancimat conditions at 100°C; the stability decreased by 29-65% of the original value, and the tocopherol content by 5-61% during 15 min heating (MARINOVA et al 2001).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…The highest peroxide value was found for the extra virgin sunflower oil enriched in carotenoids by the MAE of dry tomato waste, a fact that is in agreement with the highest content of polyunsaturated fatty acids of this oil among the three investigated oils. Hassanein et al, (2003) also reported that in vegetable oils exposed to microwave energy, the higher the oil content in polyunsaturated fatty acids, the greater the rate of oils' quality deterioration.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…Since its invention and development, the use of the microwave oven increased constantly, both at home and in the industry sector, due to its advantages, that includes capacity to rapidly transmit heat due to its high penetration power (Hassanein et al, 2003;Burfoot et al, 1990), convenience, ease of use (Caponio et al, 2003;Cossignani et al, 1998) and time and energy savings (Albi et al, 1997a). Another reason to the constant increase in the use of the microwave oven is the tendency of the industry to produce pre-prepared food products especially to defrost, heat or cook using this kind of equipment (Albi et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%